THE EFFECT OF ADDITIONAL ANCHOVY FLOUR (Stelephorus commersonii) ON THE PROCESSING OF DRIED CREAM PUFF ON CONSUMER ACCEPTANCE - Muhammad Ihsan; Sumarto Sumarto; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis study aimed to determine the effect of consumer acceptance on dried cream puff with the addition of anchovy flour. The research method used was the experimental processing of dried cream puff with different concentrations of anchovy flour. The research data were analyzed using a one-factor completely randomized design. The test parameters were organoleptic analysis (appearance, aroma, taste and texture), proximate analysis (moisture content, ash content, fat content, protein content and calcium content). Research showed that the addition of anchovy flour had  affected on the flavor of the dried cream puff produced. The use of a concentration of 15% anchovy flour was the best treatment with characteristics, namely: it had a brownish yellow appearance, the aroma of anchovy quite strong, the taste of anchovy flour was felt, the texture was dry, tasty. The result of proximate analysis was the moisture content of 8.19%, the ash content of 5.19%, the fat content of 26.12%, the protein content of 16.46% and the calcium content  of 49.68%.Keywords: anchory, dried cream puff,, taste